DAMPAK MODAL SOSIAL (LENGGE) TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT TANI (Studi Kasus pada Komunitas âLenggeâ di Kabupaten Bima) - , Adhie Aulia, Dr. Poppy Ismalina, M.Ec ([Yogyakarta] : Universitas Gadjah Mada, 2011)
For those of agricultural society, agriculture is part of their life, even a way of life. In addition to economic aspects, social aspects such as cultural and religious beliefs and traditions, play an important role in the actions of farmers. Agricultural community is governed by the institutions which are original and the result of cultural work. The existence of Lengge (communal granary) which is a cultural product of the past will bear the specific social interaction of Maria villageâs society, Wawo sub district, Bima. This research is aimed to identify the behavior of Maria villageâs society associated with the existence of Lengge as the center of attention. The suitability between informal norms as a social interaction effects and characteristics of social capital will be seen. In the end, it will be proved whether social capital of Lengge community in Maria village can encourage community economic improvement. This research is a descriptive research and the type is case study, using a quantitative approach to test various interpretations and to examine the validity / reliability as well as qualitative approach to summarize the scientific knowledge of experts in order to clarify the phenomenon under the research. To obtain data, questionnaire instrument is done using respondents which are selected through random sampling method as well as in-depth interviews using informants which are selected through the purposive sampling. The technique of quantitative data analysis begins with testing the validity and reliability, then the data questionnaire which have been valid and reliable regression analysis was performed simultaneously with a variable-veriabel economical form of land area, the amount of labor and production costs. While the qualitative data will be reduced (data reduction), is presented (data display) and inferred from the interpretation and analysis in depth. The result shows that the dimension of the network, cooperation, trust and perspective toward the local area of Lengge community in Maria village, Bima begins with the kinship pattern model which arouse the classification of exchange model reciprocally. It also ranks the allocations of money obtained by connecting the pattern of exchange with the allocations of money. From the analysis of patterns of exchange relationship with the allocations of money led to a model of social interaction as a raw material that is able to build social networks, cooperation, trust, and positive perceptions of the environment is occupied. The quantitative result obtained indicates that social capital significantly influence the increase of income. However, direct social capital variables are not correlated positively with higher income, because the social capital that is formed has not been directed to things that are economical but still part of the happiness of life